Psychological and Religious Perspectives on Emotion - Watts, Fraser N. (Zygon, 1997)
This article is devoted to examining theoretical issues on the interface of the psychology of religion and the psychology of emotion, something which recently has been surprisingly neglected. The broad range of psychological components involved in emotion, and the importance of emotional processes in religion, make it a particularly relevant area of general psychology as far as religion is concerned. The first issue to be examined is the centrality of emotion (or feeling) in religion and the extent to which religion can be conceptualized as a kind of emotional state—an idea that can be found in different forms in Schleiermacher and James. Though both psychology and emotion are now seen as less private than previously supposed, the analogy remains potentially fruitful. The second issue arises from the notable tendency in the psychology of emotion to see emotion as functional, even rational, rather than disruptive. The view of Averill is endorsed that emotions can be psychologically creative when used appropriately. This leads to a review of attitudes toward emotional aspects of religion and religious attitudes to everyday emotions, where a positive but discriminating approach to emotions seems appropriate.